2022
DOI: 10.3390/children9071016
|View full text |Cite
|
Sign up to set email alerts
|

Apophyseal Avulsion of the Rectus Femoris Tendon Origin in Adolescent Soccer Players

Abstract: Apophyseal avulsions of the rectus femorus tendon (RFT) at the anterior inferior iliac spine (AIIS) can occur in adolescents, often while performing soccer. Patient-reported outcomes (PROMs) and time to return to sport of these patients are relatively unknown. Therefore, the aim of this study was to assess the PROMs and return to sports of patients with AIIS avulsions and compare the results with those reported in the literature. This is a case series of seven consecutive patients presenting at our hospital be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The anterior inferior iliac spine (AIIS) is a frequent site of avulsion fracture in the pelvis in teenage athletes where the hormonally induced muscle strengthening coexists with secondary ossification at the apophyses [ 3 ]. Most pelvic avulsion fractures, including AIIS, are treated successfully nonoperatively, using analgesics, bed rest, immobilization of the affected muscle group, physical rehabilitation, and crutches for at least 3–6 weeks post-injury [ 1 , 6 8 ]. Although, avulsion fractures of the pelvis have been biologically assimilated to epiphyseal fractures and are naturally prone to bone healing [ 4 ], repetitive traumatism, due to muscle traction over the avulsed fragment, often leads to hypertrophic healing, bulking, and appearance that may mimic bone tumours, especially when a delayed diagnosis or no supervised conservative treatment is made [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anterior inferior iliac spine (AIIS) is a frequent site of avulsion fracture in the pelvis in teenage athletes where the hormonally induced muscle strengthening coexists with secondary ossification at the apophyses [ 3 ]. Most pelvic avulsion fractures, including AIIS, are treated successfully nonoperatively, using analgesics, bed rest, immobilization of the affected muscle group, physical rehabilitation, and crutches for at least 3–6 weeks post-injury [ 1 , 6 8 ]. Although, avulsion fractures of the pelvis have been biologically assimilated to epiphyseal fractures and are naturally prone to bone healing [ 4 ], repetitive traumatism, due to muscle traction over the avulsed fragment, often leads to hypertrophic healing, bulking, and appearance that may mimic bone tumours, especially when a delayed diagnosis or no supervised conservative treatment is made [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the growth plate is biomechanically weaker than the tendon, direct injury during adolescence results in avulsion displacement of the epiphysis rather than tendon rupture. As there are at least two more proximal tendons (indirect head and reflected head), the apophyseal displacement in the case of direct tendon avulsion is small and usually recovers well with conservative treatment with rest [28]. Operative treatment is reserved for widely displaced fractures (> 2 cm displacement) or when late complications such as heterotopic ossifications occur [28].…”
Section: Introductionmentioning
confidence: 99%
“…As there are at least two more proximal tendons (indirect head and reflected head), the apophyseal displacement in the case of direct tendon avulsion is small and usually recovers well with conservative treatment with rest [28]. Operative treatment is reserved for widely displaced fractures (> 2 cm displacement) or when late complications such as heterotopic ossifications occur [28]. US allows imaging of the anatomy of the avulsion chain in detail due to high spatial resolution, thus allowing early diagnosis and recognition of the extent of apophyseal displacement [27].…”
Section: Introductionmentioning
confidence: 99%
“…Descending further in the human body, two studies investigated lower extremity injuries. Weel et al [ 20 ], in a long-term retrospective study, obtained patient-reported outcomes of adolescent soccer players with avulsion fractures of the anterior inferior iliac spine at the origin of the rectus femoris. Of seven initially nonoperatively treated patients, one required surgical excision of a heterotopic ossification.…”
mentioning
confidence: 99%